Komparasi Kinerja Keuangan Lembaga Amil Zakat - Prayogo P. Harto; Vivi Sufi Anggraeni; Ainur Bayinah (Jurnal Akuntansi dan Keuangan Islam, 2018)
This study aims to determine the financial performance of zakat institutions. Measurement of financial performance by using financial ratios listed in the International Standard of Zakat Management (ISZM). The financial ratio consists of components of efficiency and capacity. The Objects used in this study are financial and/or annual report of zakat institutions. The results of this study indicate that in terms of efficiency, the institutions of zakat can be said to have been efficient in carrying out its operational activities, but in terms of capacity should still be improved.